Evaluation of fine needle aspiration cytology of lymph nodes in Kathmandu Medical College, Teaching hospital - Hirachand, S; Lakhey, M; Akhter, J; Thapa, B (Kathmandu University Medical Journal, 2010)
Background: Fine Needle Aspiration Cytology (FNAC) is a simple and rapid diagnostic technique. Because of early availability of results, simplicity, minimal trauma and complications, the aspiration cytology is now considered a valuable diagnostic aid and is part and parcel of a pathologist's repertoire. Objectives: The aim of the study was to evaluate the results of fine needle aspiration cytology (FNAC) of lymph nodes in our institution in comparison to result of histopathology. Materials and methods: The present study on 130 patients of lymphadenopathy was conducted in the Department of Pathology Kathmandu Medical College Teaching hospital, Kathmandu from June 2006 to May 2008 (2 years). Results: In this series of FNAC cervical lymph nodes were 66 (50.76%), and axillary lymph nodes were 20 (15.38%). Male to female ratio of the patients was 1: 0.9. Th age of patients ranged from 3 to 85 years. FNAC diagnosis was found to be as follows : reactive hyperplasia 54( 41.55%), tubercular lymphadenitis 36 (28 %), metastatic carcinoma 16 (12.3%), granulomatous lymphadenitis 12 ( 9.2 % ), lymphoma 8 (6%) and suppurative lymphadenitis 4(3%). Out of 28 cases of FNAC 26 (92.85%) were consistent with histopathological diagnosis of tubercular lymphadenitis. In metastatic carcinoma to lymph nodes sensitivity and specificity of FNAC were 100% each. Conclusion: FNAC is useful and reliable in diagnosing neoplastic and non- neoplastic lesions of lymph nodes. It helps in planning surgery for malignant cases, where definitive operative intervention can be performed in one session. Key words: FNAC; lymphadenopathy. DOI: 10.3126/kumj.v7i2.2707 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26,139-142